pH сенсорные материалы на основе полимерных наноразмерных структур - Безкровная, О.Н.; Мчедлов-Петросян, Н.О.; Водолазкая, Н.А.; Литвин, П.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The possibility of the fabrication of Langmuir–Blodgett polyamic acid-based dye-containing pH-indicative films is demonstrated. The lipoidal dyes, n-decyl fluorescein and n-decyleosin immobilized in a polymeric multilayer nanosized structure, exhibit changes in absorption and emission within a pH range from 1 to 10, which can be used in sensor devices.